Efek Mediasi Self Efficacy Terhadap Penerapan Etika Dalam Pendidikan Akuntansi - Vadelin Vadelin; Clara Susilawati (Universitas Katolik Soegijapranata Semarang, 2019)
This study discusses the literature gap by investigating the role of self-efficacy of lecturers in applying ethics in the accounting curriculum. The concept of self-efficacy, in this study defines the self-efficacy of accounting lecturers to apply ethics in lectures as